Impact of prehospital opioid dose on angiographic and clinical outcomes in acute coronary syndromes. Issue 2 (26th April 2022) - Fernando, Himawan; Nehme, Ziad; Dinh, Diem; Andrew, Emily; Brennan, Angela; Shi, William; Bloom, Jason; Duffy, Stephen James; Shaw, James; Peter, Karlheinz; Nadurata, Voltaire; Chan, William; et al.
Abstract : Background: An adverse interaction whereby opioids impair and delay the gastrointestinal absorption of oral P2Y12 inhibitors has been established, however the clinical significance of this in acute coronary syndrome (ACS) is uncertain. We sought to characterise the relationship between prehospital opioid dose and clinical outcomes in patients with ACS. Methods: Patients given opioid treatment by emergency medical services (EMS) with ACS who underwent percutaneous coronary intervention (PCI) between 1 January 2014 and 31 December 2018 were included in this retrospective cohort analysis using data linkage between the Ambulance Victoria, Victorian Cardiac Outcomes Registry and Melbourne Interventional Group databases. Patients with cardiogenic shock, out-of-hospital cardiac arrest and fibrinolysis were excluded. The primary end point was the risk-adjusted odds of 30-day major adverse cardiac events (MACE) between patients who received opioids and those that did not. Results: 10 531 patients were included in the primary analysis. There was no significant difference in 30-day MACE between patients receiving opioids and those who did not after adjusting for key patient and clinical factors. Among patients with ST-elevation myocardial infarction (STEMI), there were significantly more patients with thrombolysis in myocardial infarction (TIMI) 0 or 1 flow pre-PCI in a subset of patients with high opioid dose versus no opioids (56% vs 25%, p<0.001). This remained significant after adjusting for known confounders with a higher predicted probability of TIMI 0/1 flow in the high versus no opioid groups (33% vs 11%, p<0.001). Conclusions: Opioid use was not associated with 30-day MACE. There were higher rates of TIMI 0/1 flow pre-PCI in patients with STEMI prescribed opioids. Future prospective research is required to verify these findings and investigate alternative analgesia for ischaemic chest pain.